Omkering Van Bewijslast Dalam Tindak Pidana Pencucian Uang Di Indonesia Berdasarkan Prinsip Persumption Of Guilty - Puspitasari Rusdi; Fakhril Riadi Mursalim (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Omkering van bewijslast is referred to as the principle of reversal of the burden of proof or reverse proof. The application of reverse evidence is carried out by the judge ordering him to prove that his property was obtained legally. Article 77 of the Money Laundering Crime Law has inspired the reverse burden of proof in Indonesia. However, the concept of the reverse burden of proof is balanced and limited, so it is important to reformulate the reverse burden of proof based on the principle of presumption of guilt, which will effectively refer to predicate crimes. The burden of proof is reversed based on the principle of presumption of guilt which will have an unlimited nature for the Crime of Money Laundering and adopting the taint doctrine for assets tainted by the Crime of Money Laundering. In this article, we will examine the regulation of the reversal of the burden of proof in the crime of money laundering in Indonesia and the application of the reverse burden of proof based on the principle of presumption of guilt in cases of the crime of money laundering in Indonesia. The research method used is a normative legal research method through a statutory approach and a case approach. The legal materials used are primary legal materials and secondary legal materials using literature review and then analyzed prescriptively.